Understanding Media and Refugees Through Civil Society: Multeci-Der Case - GÜRAN YİĞİTBAŞI, KÜBRA (MARMARA UNIV, FAC COMMUNICATION, 2016)
Media allows us to witness to the moments - to the wars in which humanity remains most embarrassed, most vulnerable and most desperate - today via the latest technologies. It is known that the Gulf War was a turning point in media's illustration of a war, meaning that its representation of actual war footage as a cinematography to the audience in a way never seen before. The point where we have arrived at today seems that it has gone beyond watching the war in our safe places by feeling as if we were directly involved in it. Media receivers/target audiences are now facing the witnessing and being aware of the incidents that all civilians -especially the most affected ones, children, women and elderly people-experienced. This situation brings along the demands of societies who are willing to take responsibilities and initiatives about the events they witnessed, besides the countries and the governments. In this study, the extent to which Multeci-Der as a non-governmental organization that works for refugee problems can represent itself in the media is analyzed by content analysis and discourse analysis methods. In what extent the association is represented and with what types of news it is represented is considered significant, since it shows Multeci-Der's contributions for creating an agenda on the subject. With reference to the ongoing war in Syria since 2011, the media news regarding Syrian refugees have been analyzed over Multeci-Der, which was established as a non-governmental organization in order to work for refugees. As a result, it is seen that the national press reserves a limited attention about the association's activities and statements, and the news of local press seem to be far from creating an agenda and public opinion throughout the country.
Keywords: Refugees; Public Opinion; Agenda Setting; Refugee Policies